2012
DOI: 10.4067/s0717-97072012000100005
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Resistance of Decorative Chromium Films Obtained From Trivalent Chromium Solutions

Abstract: In this work, the resistance to corrosion of chromium films obtained from trivalent chromium solutions of different compositions and the influence of solution compounds on the coatings electrochemical behavior and the microstructure were studied. The chromium coatings were obtained from trivalent solutions in a chloride-based bath with different complexing agents adding also sodium hypophosphite and aluminum chloride. UV-vis spectroscopy was carried out on all solutions before and after plating to observe chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 17 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…It was also found that the presence of traces of Fe in the bath, generally in the range of 150 mg l −1 , could be beneficial to the final properties (including corrosion) of the Cr coatings. 18 There are studies evaluating the corrosion resistance of Cr(III)based electrodeposits 6,[19][20][21] where some of them claim a better corrosion resistance when using a proper amount of Fe 2+ ions in the bath. 22 However, such studies are mainly based on the overall performance of a multilayer nickel-chromium system 23 rather than evaluating the behaviour of a single chromium coating and its passive layer.…”
mentioning
confidence: 99%
“…It was also found that the presence of traces of Fe in the bath, generally in the range of 150 mg l −1 , could be beneficial to the final properties (including corrosion) of the Cr coatings. 18 There are studies evaluating the corrosion resistance of Cr(III)based electrodeposits 6,[19][20][21] where some of them claim a better corrosion resistance when using a proper amount of Fe 2+ ions in the bath. 22 However, such studies are mainly based on the overall performance of a multilayer nickel-chromium system 23 rather than evaluating the behaviour of a single chromium coating and its passive layer.…”
mentioning
confidence: 99%